Impact Of Percapita Expenditure And Inflation On Poverty In Pekanbaru City : (Before And After The Covid-19 Pandemic) - Herman, Herman (International Journal of Islamic Business and Management Review, 2022)
This study aims to determine the impact of per capita spending and rising inflation on poverty in the city of Pekanbaru. Secondary data for the period 2012-2021 is from the Central Statistics Agency of Pekanbaru City. The data analysis method used multiple linear regression. The results of the descriptive research show that the average number of poor people is 3.2010 people, per capita expenditure is 1.4339 and inflation is 0.53 percent. And the results of the study showed that per capita expenditure before the covid-19 pandemic had no effect, while after the covid-19 pandemic there was an effect on the number of poor people, and the increase in inflation before and after the covid-19 pandemic had an effect. Meanwhile, the results of simultaneous research before the covid pandemic had no effect, while after the covid-19 pandemic, all independent variables had an effect on the dependent variable.